DESCRIPTION OF IRON SELENIDE THIN FILMS DEVELOPED BY CHEMICAL METHOD AT ROOM TEMPERATURE (International Journal of Food and Nutritional Sciences, 2022)
Nanostructured materials have indeed become a very active research field in the areas of solid state physics, solid state chemistry, solid state ionics, material engineering and biotechnology. Iron selenide thin films have been set down onto glass substrates by the chemical deposition techniques. To obtain good quality FeSe thin films, preparative conditions such as concentration of cationic and anionic precursors, adsorption and rinsing time durations etc are optimized. Structural characterization of iron selenide thin films was carried out by means of X-ray diffraction. The morphological characterization of FeSe thin film was carried out using scanning electron microscopy. The semiconducting behavior of FeSe thin films has been studied by using two probe method of electrical resistivity.